Community Participation in the Management of Sumber Maron Natural Tourism as an Independent Tourism Village in Karangsuko Village Pagelaran District Malang Regency - Wahyuni, Riska Dea Sri; Zulkarnain, Zulkarnain; Raharjo, Kukuh Miroso (Proceedings Series of Educational Studies, 2024)
This research aims to (1) describe the process of implementing the management of Sumber Maron natural tourism as an independent tourist village in an effort to empower the local community of Karangsuko Village. (2) Describe the of community participation in the management of Sumber Maron natural tourism. The method used in this research is qualitative research approach and utilizes the case study research type. The researcher collacted data using data collection tehniques through interviews, observations, and usin documentary studies. In this study, the researcher collected data through key informants primarily by conducting interviews using an interview guide. The results of this study indicate that the research used field findings including (1) the tourism management process of Sumber Maron starting from the intial stage of planning, such as socialization. The second stage is organizing, whic involves establishing the village-owned enterprise institution, known as BUMDes (Village-Owned Enterprises). The final stage is evaluation, conducted through avillage consultation meeting (MusDes) attended by the community, cillage officials, business unit leaders, employees, and community leaders of Karangsuko vllage. (2) in this study, the community participation of Karangsuko Village in manging the natural tourism of Sumber Maron is analyzed based on levels of participation from planning to evaluation. Partisipatiory learning occurs through technical guidance activities in the from of training for managers and employees involved in manging Sumber Maron Tourism. Keywords: community partisipasion, tourism management, tourism village.